Fragmento d'alma - Silva, Bruno Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Fragmento D' Alma is an artistic research that part of a poetic tale through an initial charge of dawn one fantastic universe where words have life and willingly. The work includes sculptural works in order to interpret through the use of allegory situations of the tale in the form of sculptural compositions considering one or more characters in the story. In the sculptural work, I tried figuring the relations tale as my interpretations and poetic, so I sought theoretical studies of allegory after noting my affinity with the theme to contribute to the relationship text and image set in my work. I also sought to understand the relationships that the text played with sculptural work, so the chances that I could address this through dialogue between text and image. The studies collected through surveys pointed allegory by João Adolfo Hansen, as well as in various artistic and visual references present in my repertoire, such as the Baroque sculpture of Bernini, the performances of Berna Reale and literature of Neil Gaiman, contributed in this research to the development of my creative process during the preparation of this research work of art, making the complexity of the relationship between textual production and poetic sculptural three-dimensional, also became a concern and an integral theme of my work and my reflections presented here. Therefore, I conclude based on my own experience in this work, the artistic research inspired allegory might contribute to the development of my creative process during the preparation of this artwork, besides assigning relations between textual production and poetic dimensional sculpture

Fragmento D’Alma é uma pesquisa artística que parte de uma poética inicial através de um conto responsável por despontar um universo fantástico aonde palavras possuem vida e vontade própria. O trabalho conta com obras escultóricas a fim de interpretar através do recurso da alegoria as situações do conto em forma de composições escultóricas considerando uma ou mais personagens da estória. No trabalho escultórico, busquei figurar as relações do conto conforme minhas interpretações e poéticas, assim busquei embasamento teórico na alegoria após notar minha afinidade com o tema a fim de contribuir para as relações texto imagem estabelecidas em meu trabalho. Também procurei compreender as relações que o texto desempenhava com a obra escultórica, logo nas possibilidades que eu poderia abordar através desse dialogo entre texto-imagem. Os estudos levantados através das pesquisas sobre alegoria apontadas por João Adolfo Hansen, bem como em diversas referências artísticas e visuais presentes em meu repertório, tais como a escultura barroca de Bernini, as performances de Berna Reale e a literatura de Neil Gaiman, contribuíram nesta pesquisa, com o desenvolvimento de meu processo criativo, durante a elaboração desse trabalho de pesquisa artística, fazendo com que a complexidade das relações entre uma produção textual e a poética tridimensional escultórica, se tornassem também uma preocupação e tema integrante de meu trabalho e de minhas reflexões, aqui apresentados. Para tanto, concluo baseado em minha própria experiência adquirida nesse trabalho, que a pesquisa artística inspirada na alegoria pôde contribuir com o desenvolvimento do meu processo criativo, durante a elaboração deste trabalho artístico, além de atribuir relações entre uma produção textual e a poética tridimensional escultórica
Keywords: Arte e literatura; Alegorias; Contos; Escultura; Allegories